2014
DOI: 10.1002/chem.201405501
|View full text |Cite
|
Sign up to set email alerts
|

An Enolate‐Mediated Organocatalytic Azide–Ketone [3+2]‐Cycloaddition Reaction: Regioselective High‐Yielding Synthesis of Fully Decorated 1,2,3‐Triazoles

Abstract: An enolate-mediated organocatalytic azide-ketone [3+2]-cycloaddition (OrgAKC) reaction of a variety of enolizable arylacetones and deoxybenzoins with aryl azides was developed for the synthesis of fully decorated 1,4-diaryl-5-methyl(alkyl)-1,2,3-triazoles in excellent yields with high regioselectivity at 25 °C for 0.5-6 h. This reaction has an excellent outcome with reference to reaction rate, yield, regioselectivity, operation simplicity, and availability of substrates and catalyst. This reaction has advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(25 citation statements)
references
References 80 publications
0
25
0
Order By: Relevance
“…Triazoles 1-6 were synthesized using a metal-free domino reaction from aryl trifluoromethyl ketones and aryl azides in the presence of a base (DBU or triethylamine) in a 1:1:3 ratio (Sosnovskikh & Usachev, 2002;Usachev et al, 2011Usachev et al, , 2014. Triazole 7, which contains a hydroxy group, was prepared at room temperature using a catalytic amount of base DBU or trimethylamine from enolizable aryl trifluoromethyl ketones and aryl azides (Shashank et al, 2014) (Fig. 3).…”
Section: Figurementioning
confidence: 99%
“…Triazoles 1-6 were synthesized using a metal-free domino reaction from aryl trifluoromethyl ketones and aryl azides in the presence of a base (DBU or triethylamine) in a 1:1:3 ratio (Sosnovskikh & Usachev, 2002;Usachev et al, 2011Usachev et al, , 2014. Triazole 7, which contains a hydroxy group, was prepared at room temperature using a catalytic amount of base DBU or trimethylamine from enolizable aryl trifluoromethyl ketones and aryl azides (Shashank et al, 2014) (Fig. 3).…”
Section: Figurementioning
confidence: 99%
“…Further experiment revealed that CHCl 3 was the best solvent for this transformation. When we conducted the reaction using 35 CHCl 3 as the solvent, the excellent yield (93%) was observed (Table 1, entry 16). Further extensive screening of temperature indicated that decreased T o C led to a slow conversion (entry 17, 50 o C, 53%, 48 h).…”
Section: Entry 5) Other Amine Catalysts (I-iv Vi-viii)mentioning
confidence: 98%
“…1a bearing a LG group (MeO) was chosen to demonstrate the reaction process. DBU would firstly react with 1a to form zwitterion D. In summary, a DBU-catalyzed organocatalytic 1,3-dipolar 35 cycloaddition of active α, β-unsaturated ester to azide has been developed. This methodology provides a straightforward pathway to generate 1,4-disubstituted 1,2,3-triazoles, which exhibit considerably biological activities, in high yields and regioselectivities.…”
Section: Entry 5) Other Amine Catalysts (I-iv Vi-viii)mentioning
confidence: 99%
“…The presence of copper might interfere with cellular functions and limit the application of the metal‐catalyzed cycloaddition in biological systems ,. Alternatively, metal‐free strategies (organocatalytic or base‐mediated) have emerged to provide diversely substituted triazoles, using different dipolarophiles, such as enamines or enolates from readily available carbonyl compounds or activated alkenes (Scheme b‐1d) …”
Section: Introductionmentioning
confidence: 99%